Improved Learning Outcomes of Basketball Material Students through Blended Learning Model with EUKBM Media against Students of Class X MIPA Daughter SMAN 1 Tuban - Imam Syafi’i; Nurkholis Nurkholis; Agus Hariyanto; Abdul Rachman Syam Tuasikal; Nanik Indahwati; Gigih Siantoro (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The educational problems experienced in Indonesia are many, one of which is the Covid-19 pandemic. With the Covid-19, school learning has obstacles until the learning process cannot be done completely, both structural and non-structural learning. The study used a short series of kuantitatf statistics with quasi-experimental research models and used control groups of pretest-posttes design because the study applied pretest before being given treatment and provided post test after treatment. The study was conducted at SMAN 1 Tuban. The subject of this study was a student of class X MIPA daughter SMAN 1 Tuban. The study also included three variables including learning outcomes from attitude values, knowledge values and skill values. The results of research that has been obtained state that the blended learning model with EUKBM media has a significant influence on learning outcomes. This can be known from the average pretest and postest knowledge scores between the experimental class and the control class. Through the application of blanded learning researchers also found changes in attitudes, behavior, knowledge and also skills of students during the learning process. Students become more participating and interacting with teachers and other students. Through the development of this blended learning model, students are more active when learning both online and offline. So that in the process of his defense does not seem monotonous.